Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1974
DOI: 10.1172/jci107535
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Cyclic Nucleotides in Plasma

Abstract: A B S T R A C T In order to determine the sites of net production and removal of the cyclic nucleotides in plasma, various blood vessels were catheterized in 17 anesthetized dogs and arterial and venous concentrations of adenosine 3',5'-monophosphate (cAMP) and guanosine 3',5'-monophosphate (cGMTP) were measured by radioimmunoassay.Aortic cAMP was 30±2 nM (mean±SE) and cGMP was 13+1 nM. There were no significant differences for either cyclic nucleotide between the concentration in the aorta and that in the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

1974
1974
1986
1986

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 14 publications
(16 reference statements)
1
17
0
2
Order By: Relevance
“…As in humans, urinary clearance accounted for only 15 (19). A balance between uptake and secretion of cyclic nucleotide by the liver may account for the observation reported in the accompanying paper (7), that there is no large concentration difference of cAMP between hepatic artery, superior mesenteric vein, and hepatic vein.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…As in humans, urinary clearance accounted for only 15 (19). A balance between uptake and secretion of cyclic nucleotide by the liver may account for the observation reported in the accompanying paper (7), that there is no large concentration difference of cAMP between hepatic artery, superior mesenteric vein, and hepatic vein.…”
Section: Discussionmentioning
confidence: 71%
“…Our investigation of the clearance of plasma cyclic nucleotides by the kidney in the dog were prompted by the observation that cyclic nucleotide concentration in renal venous plasma was substantially less than that in arterial plasma (7). We have shown that in the dog the plasma cyclic nucleotides are also in a dynamic steady state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no established theory for the origins of c-AMP and c-GMP in plasma, though exten sive studies in this problem were reported by Wehmann, (1974). Nevertheless, it is generally considered that plasma cyclic nucleotides re flected their concentrations within cells to some extent, and diffusion of these cyclic nucleotides through the cell membrane was actually observed.…”
Section: Discussionmentioning
confidence: 99%
“…By substituting 0.120 liter/min for kidney clearance (3) and using other normal values from Table III, it can be seen that if metabolic clearance and production were unchanged, the absence of kidney clearance would result in a concentration of cyclic AMP equal to: 13.6 X (0.624 -0.120)-1= 27 nM. support the finding of the present study that a reduction in glomerular filtration rate cannot entirely account for the degree of elevation of plasma cyclic AMP. Recently, Wehmann, Blonde, and Steiner (28,29), using infusions of tritiated cyclic nucleotides in dogs, observed that urinary excretion accounted for only about two-thirds of the total kidney clearance of cyclic AMP, extraction of the nucleotide by renal parenchymal tissue apparently accounting for the remainder. A significant role of renal extraction, in contrast to excretion, was also demonstrated by the experiments of Coulson, RochRamel, and Bowman, who studied the disappearance of ['H]cyclic AMP from plasma before and after nephrectomy in rats (30) and by those of Coulson and Bowman (31), who studied the handling of extracellular cyclic AMP by the perfused rat kidney.…”
Section: Discussionmentioning
confidence: 99%